Status of External and Internal Labor Migration in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In recent years, Uzbekistan has been paying serious attention to creating new jobs and ensuring the stability of existing jobs in order to increase employment and economic activity. The main focus is on reducing unemployment, ensuring the employment of graduates of educational institutions entering the labor market for the first time, increasing the employment of vulnerable groups, in particular, women, people with disabilities, convicts, victims of human trafficking, external migration and others. In this regard, the normative legal acts adopted in recent years define a number of important tasks facing the Ministry of Employment and Labor Relations of the Republic of Uzbekistan.